2017
DOI: 10.1287/mnsc.2016.2520
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Choice Models with Endogenous Network Effects

Abstract: Network externality arises when the utility of a product depends not only on its attributes but also on the number of consumers who purchase the same product. In this paper, we study consumer choice models that endogenize such network externality. We first characterize the choice probabilities under such models and conduct studies on comparative statics. Then we investigate the assortment optimization problem under such choice models. Although the problem is generally NP-hard, we show that a new class of assor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…They found that the optimal prices might be different when network effect existed even for homogeneous case. Different from the literature Du et al [9], Wang and Wang [1] investigated the assortment optimization problem under MNL with endogenous network effects. They found that the quasi-revenue-ordered assortment was optimal under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that the optimal prices might be different when network effect existed even for homogeneous case. Different from the literature Du et al [9], Wang and Wang [1] investigated the assortment optimization problem under MNL with endogenous network effects. They found that the quasi-revenue-ordered assortment was optimal under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We next analyze the influence of the product's quality on the optimal solutions when the network effect exists. We assume the product's quality lies in [1,10]; let = −2, = 1, = 1, and V 0 = 0.5. Figure 2 shows the variation of optimal solutions with the quality.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 3 more Smart Citations